TRADITIONS OF SCHOOL EDUCATION OF THE LOWER TEREK COSSACKS (19th - early 20th cent.) - Gimbatova, M B (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers traditional schooling of the Lower Terek Cossacks, formation and development of parochial, primary, garrison schools and secular vocational schools, the procedure and conditions for rendering of education services.The author of the article presents the features of male and female education, considersimplementation of modern teaching methods, introduction of mixed schools for co-education of boys and girls, availability of educational programs, which include general subjects, basics of Orthodoxy, lessons of labor, physical and aesthetic education, and presence of special classes and libraries. Government support of the Russian population of the Lower Terek has contributed to the increase in the number of educational institutions and the growth of literacy among the population.
Keywords: Lower Terek Cossacks; education; primary school; college; students; Kizlyar; Terek region; teaching methods; educational process